The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.12840/issn.2255-4165.2016.04.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of narrative interventions and health effects: A review of the content, form, and context of narratives in health-related narrative persuasion research

Abstract: In recent years, many studies have been conducted on persuasive effects of narratives in a health context. A striking feature of this research area is the diversity of the narratives that are used in the various studies. Narratives that convey a health message differ widely on a large number of dimensions related to the content, form and context. We expect that these characteristics are potential explanatory factors in the effectiveness of the narratives. To provide an overview of the different characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 38 publications
3
58
0
8
Order By: Relevance
“…In line with the existing literature, the aspects that participants mentioned as having affected them most, involved strong emotions as shown here, emphasising that highly emotional narratives are effective. 4,10 It is important to note that whereas the given studies involved constructed stories and took a quasi-experimental approach, the results were similar to this study in which participants spontaneously related their experiences without being scripted. Three strong emotions arose out of the narratives, that is, sadness, contentment and fear.…”
Section: Fearsupporting
confidence: 67%
See 3 more Smart Citations
“…In line with the existing literature, the aspects that participants mentioned as having affected them most, involved strong emotions as shown here, emphasising that highly emotional narratives are effective. 4,10 It is important to note that whereas the given studies involved constructed stories and took a quasi-experimental approach, the results were similar to this study in which participants spontaneously related their experiences without being scripted. Three strong emotions arose out of the narratives, that is, sadness, contentment and fear.…”
Section: Fearsupporting
confidence: 67%
“…The effects of the narratives mostly lay in the emotions that were provoked amongst the participants, which are in line with literature. 4,9 Some responses by participants show that they were transported into the experiences of the speakers, thus making the narratives more memorable to them 4 buoyed by the fact that the speakers live to tell their stories. 1 Reactions by students detailing the behavioural changes that they intend to make show that they did not merely listen to the narratives, but that they adapted them with the intention of making necessary changes to their lives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In entertainment education narratives, the embedded message is often communicated via the protagonist's behavior. Such behaviors can be framed in a positive way, by showing the positive consequences of a recommended behavior such as positive emotions and social acceptance; in a negative way, by showing the negative consequences of undesired behavior such as negative emotions and social rejection (De Graaf et al, 2016). Several studies have shown that positively framed narratives, i.e., narratives that show the positive consequences of a recommended behavior, increased children's character strengths (Du & Hao, 2018;Lee et al, 2014;Talwar et al, 2016).…”
Section: Systematic Cognitive Processes: Moral Reasoningmentioning
confidence: 99%